2015
DOI: 10.1007/s00122-015-2628-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and mapping of Tril, a homeodomain-leucine zipper gene involved in multicellular trichome initiation in Cucumis sativus

Abstract: Fruit spines are a special type of trichome that impacts the quality and appearance of cucumber (Cucumis sativus L.) fruit. Scanning electron microscopy revealed that the trichome-less (tril) mutant originating from European greenhouse cucumber has a completely glabrous phenotype on cotyledons, hypocotyls, young leaves, fruits, and fruit stalks. Genetic analysis revealed that tril was inherited as a recessive allele at a single locus. Using 1058 F2 individuals derived from a cross between cucumber tril mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 34 publications
1
78
1
Order By: Relevance
“…Five trichome-related mutants of the genes CsGL3, TRIL, MICT, TBH, and CsGL1, all of them encoding homeodomain-Leu zipper transcription factors from different subfamilies, have been reported in C. sativus (Chen et al, 2014;Li et al, 2015;Pan et al, 2015;Zhao et al, 2015;Cui et al, 2016;Wang et al, 2016b). Based on the observed phenotypes, a molecular mechanism underlying the development of multicellular trichomes in this species has been proposed in a recent review and seems to confirm that the transcriptional control of multicellular trichomes in C. sativus differs from the one observed in Arabidopsis.…”
Section: A Detailed Understanding Of Glandular Trichome Initiation Anmentioning
confidence: 99%
“…Five trichome-related mutants of the genes CsGL3, TRIL, MICT, TBH, and CsGL1, all of them encoding homeodomain-Leu zipper transcription factors from different subfamilies, have been reported in C. sativus (Chen et al, 2014;Li et al, 2015;Pan et al, 2015;Zhao et al, 2015;Cui et al, 2016;Wang et al, 2016b). Based on the observed phenotypes, a molecular mechanism underlying the development of multicellular trichomes in this species has been proposed in a recent review and seems to confirm that the transcriptional control of multicellular trichomes in C. sativus differs from the one observed in Arabidopsis.…”
Section: A Detailed Understanding Of Glandular Trichome Initiation Anmentioning
confidence: 99%
“…It would be of interest to investigate whether one or more additional proteins are recruited to form this complex and regulate fruit wart formation. In addition, Tril required for the initiation of multicellular trichome in cucumber is recessive and epistatic to the Mict gene (Wang et al, 2016). And in this study, the expression of Tril in the transgenic OX-1 and OX-3 lines had no obvious changes.…”
Section: The Csttg1 Gene Is Involved In a Regulatory Network Controllmentioning
confidence: 47%
“…Tu and Mict/CsGL1 were both identified, and Mict/CsGL1 was shown to be required for further differentiation of cucumber trichomes in all aerial parts of the plant, including leaves, stems, tendrils, floral organs, and fruits, but not for their initiation (Li et al, 2015;Zhao et al, 2015). Recently, a homeodomainleucine zipper gene, Tril, involved in multicellular trichome initiation in cucumber, was identified (Wang et al, 2016). However, to date, the regulatory mechanisms underlying the development of fruit bloom trichomes and warts are largely unknown.…”
mentioning
confidence: 99%
“…This is also shown by the fact that no trichomes (spines) were seen on either the foliage or the fruit surface in the glabrous mutants of cucumber (Yang et al 2011;Li et al 2015;Pan et al 2015;Wang et al 2016;Cui et al 2016). In cucumber, a number of genes related to fruit spines have been identified: B for black spine, ns for numerous spines, ss for small spines, s or s1 for spine size and frequency, s2 and s3 for dense and small spines, and gl (glabrous) and tril (trichome-less) for trichomes formation (Call and Wehner 2010;Wang et al 2016). This hypothesis was supported by data from the present study, with no observed difference in leaf trichome density but a significant difference in fruit spine density between fs1 and WT (Fig.…”
Section: Inheritance and Domestication Of Fruit Spine Density Trait Imentioning
confidence: 88%
“…Moreover, the existence of cucumber fruit spines is a precondition for the formation of fruit tubercules, as genetic analysis indicated that cucumber glabrous 1 (csgl1), a gene controlling fruit spine formation, was epistatic to the Tuberculate fruit (Tu) (Cao and Guo 1999;Cao et al 2001;Yang et al 2014;Li et al 2015). Genes gl-2, csgl1 and tril/ csgl3 controlling presence or absence of trichomes on the foliage or fruit were mapped in chromosomes 2, 3 and 6, respectively; and csgl1, tril and csgl3 were recently cloned, and both Tril and CsGL3 were found to be the same gene, Csa6M514870, in three different labs (Yang et al 2011;Li et al 2015;Pan et al 2015;Wang et al 2016;Zhao et al 2015;Cui et al 2016). Several genes related to fruit spine size and density have been identified through genetic analysis (Tkachenko 1935;Hutchins 1940;Poole 1944;Caruth 1975;Fanourakis and Simon 1987).…”
Section: Introductionmentioning
confidence: 99%